Assessment of pollution levels resulting from biomass gasification - Menya, E.; Olwa, J.; Hagstrom, P.; Okure, M. (Journal of Environmental Chemical Engineering, 2014)
In biomass gasification process the producer gas generated can be cleaned by water scrubbing. Some of the organic compounds generated are entrained together with other flue gas dust particles in to the cooling stream. The treatment / disposal of this waste stream remains a challenge because some of the compounds are toxic to humans and the environment. The objective of this study was to assess pollution levels resulting from organic constituents of flue gas filtration in a downdraft gasifier. The study involved assessment of the con- centration of polycyclic aromatic hydrocarbons (PAHs) in the liquid effluence. The impacts on human health and environment are also discussed and recommendations on measures to minimize the pollution levels are provided. A downdraft gasifier fed with maize cobs was used and condensates were collected by cooling of producer gas. Samples were preserved in a cooler at about 2 ◦C for 24 h before analysis using a capillary gas chromatographer connected to a mass spectrometer (GC–MS). The results were that concentrations of: naphthalene was 204.3 mg / m 3 , benzene 17.92 mg / m 3 , toluene 182.94 mg / m 3 , ethylbenzene 202.43 mg / m 3 , 1,2-dimethyl benzene 359.28 mg / m 3 and 1,3 + 1,4-dimethyl benzene 1016.18 mg / m 3 . It was observed that the concentrations of naphthalene and xylene were considerably higher than the recommended permissible exposure limits (PELs) on both human health and the environment. On the other hand, the concentrations of benzene, toluene, and ethylbenzene were below the PEL. Generally this study indicated that the liquid effluent meets regulatory standards, but it would be interesting to carryout tests with different biomass fuel types which this study recommends.
Keywords: Producer gas cooling; Condensate; Biomass; Downdraft gasifier